2012
DOI: 10.1080/10474412.2011.620817
|View full text |Cite
|
Sign up to set email alerts
|

Direct Behavioral Consultation in Head Start to Increase Teacher Use of Praise and Effective Instruction Delivery

Abstract: Chronic disruptive behaviors during early childhood are associated with many poor developmental outcomes including, but not limited to, school dropout and conduct disorder during adolescence. Much is known regarding effective intervention procedures for disruptive classroom behaviors by preschool children. Unfortunately, evidence-based intervention procedures may not be implemented with integrity in applied settings. Direct behavioral consultation may increase teacher intervention integrity because of direct t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
80
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 53 publications
4
80
0
1
Order By: Relevance
“…School-based consultation involves evaluating a student, teacher, or classroom's performance and providing recommendations for evidence-based strategies and supports to the teacher for improving a student or classroom's behavioral or academic performance. Therefore, school-based consultation is an indirect form of service delivery in that consultants do not work with students directly (Erchul & Martens, 2012; implementation of evidence-based strategies across a range of students (e.g., preschool, elementary, middle school, general education, and special education; Alpert & Yammer, 1983; Busse, Kratochwill, & Elliot, 1999;Dufrene et al, 2012).…”
Section: Review Of the School-based Consultation Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…School-based consultation involves evaluating a student, teacher, or classroom's performance and providing recommendations for evidence-based strategies and supports to the teacher for improving a student or classroom's behavioral or academic performance. Therefore, school-based consultation is an indirect form of service delivery in that consultants do not work with students directly (Erchul & Martens, 2012; implementation of evidence-based strategies across a range of students (e.g., preschool, elementary, middle school, general education, and special education; Alpert & Yammer, 1983; Busse, Kratochwill, & Elliot, 1999;Dufrene et al, 2012).…”
Section: Review Of the School-based Consultation Literaturementioning
confidence: 99%
“…For instance, school-based consultation can be effective for decreasing disruptive behavior (Dufrene et al, 2014;Dufrene et al, 2012;Noell, Duhon, Gatti, & Connell, 2002), increasing on-task behavior (Noell et al, 2002), decreasing the number of students referred to special education while increasing more appropriate placement rate for referred students (Fuchs, Fuchs, & Bahr, 1990;Rosenfield, 1992), and improving academic performance (Sheridan, Welch, & Orme, 1996). In fact, in a review of 10 years of school-based consultation outcome research, Sheridan et al (1996) found that 76% of the reviewed studies produced some positive results.…”
Section: Review Of the School-based Consultation Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, training alone does not create robust outcomes (Joyce & Showers, 1980. Moreover, no known empirical evidence exists that suggests simply providing teachers with didactic instruction on strategies leads to the use of strategies (DuFrene et al, 2012). Thus, it is clear that continued direct support to teachers is necessary to maintain intervention use after an initial training (Reinke, Stormont, Herman, & Newcomer, 2014).…”
mentioning
confidence: 98%
“…EID packages have demonstrated increases in the rate of child compliance of 21-49% above baseline levels (Ford et al, 2001;Mandal, Olmi, Edwards, Tingstrom, & Benoit, 2000) in classroom settings (Bellipanni, Tingstrom, Olmi, & Roberts, 2013), as well as in home and clinic settings (Mandal et al, 2000). Although EID is effective for increasing compliance, researchers have found that teachers often struggle with using and generalizing core components of the EID package, such as contingent praise (Dufrene, Lestremau, & Zoder-Martell, 2014;Dufrene et al, 2012). Furthermore, a majority of the studies have evaluated student outcomes alone.…”
mentioning
confidence: 99%